2011
DOI: 10.1089/ars.2010.3300
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminus of Heat Shock Cognate 70 Interacting Protein Increases Following Stroke and Impairs Survival Against Acute Oxidative Stress

Abstract: The decision to remove or refold oxidized, denatured, or misfolded proteins by heat shock protein 70 and its binding partners is critical to determine cell fate under pathophysiological conditions. Overexpression of the ubiquitin ligase C-terminus of HSC70 interacting protein (CHIP) can compensate for failure of other ubiquitin ligases and enhance protein turnover and survival under chronic neurological stress. The ability of CHIP to alter cell fate after acute neurological injury has not been assessed. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 53 publications
0
40
1
Order By: Relevance
“…16 Our results contrast those of Stankowski et al, 21 who reported that primary neuronal cultures transfected with a small interfering RNA (siRNA) against CHIP resulted in improved survival following oxidative stress. Such a discrepancy is likely due to their use of dissociated cell cultures, whereas we examined both in vitro and in vivo models of hypoxic responses in structured brain tissue.…”
Section: Discussioncontrasting
confidence: 99%
“…16 Our results contrast those of Stankowski et al, 21 who reported that primary neuronal cultures transfected with a small interfering RNA (siRNA) against CHIP resulted in improved survival following oxidative stress. Such a discrepancy is likely due to their use of dissociated cell cultures, whereas we examined both in vitro and in vivo models of hypoxic responses in structured brain tissue.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the benefits associated with transiently increased CHIP expression in blocking cell death induced by PD mutant genes (53), prolonged overexpression of CHIP worsens outcome following acute injury and causes proteasomal uncoupling (51), suggesting that a fine balance exists in the temporal expression of CHIP that affords neuroprotection.…”
Section: Chip-deficient Animals Have Increased Protein Oxidation and mentioning
confidence: 97%
“…We previously demonstrated that CHIP expression is increased in postmortem human tissue samples in patients following ischemic stroke as well as in an in vitro model of neuronal ischemia (51). In contrast to the benefits associated with transiently increased CHIP expression in blocking cell death induced by PD mutant genes (53), prolonged overexpression of CHIP worsens outcome following acute injury and causes proteasomal uncoupling (51), suggesting that a fine balance exists in the temporal expression of CHIP that affords neuroprotection.…”
Section: Chip-deficient Animals Have Increased Protein Oxidation and mentioning
confidence: 99%
See 2 more Smart Citations